Decoupling and decomposition analysis of CO2 emissions from government spending in China. (15th March 2022) - Cheng, Shulei; Wang, Ping; Chen, Boyang; Fan, Wei
Abstract: Exploring the role of government spending (GS) in CO2 mitigation is essential for achieving low-carbon development goals; however, the mechanism by which GS affects CO2 emissions remains unclear. The decoupling relationship between GS on energy-savings and environmental protection (GSP) and CO2 emissions in China from 2007 to 2019 was investigated. In addition to evaluating the temporal attribute of the decoupling state, the concept of a dynamic path of the decoupling state was proposed for the first time. Moreover, from the perspective of direct and indirect effects and decoupling elastic factors, the drivers of decoupling elasticity between GSP and CO2 emissions were analysed by developing two non-residual decomposition methods for the Tapio decoupling elastic index. Results based on 30 Chinese provinces showed that these provinces experienced either one or more of the decoupling states: weak, strong, expansive negative, and strong negative decoupling; however, most provinces experienced weak decoupling. Beijing, Tianjin, and Jilin were in the intensive dynamic path of the decoupling state, whereas other provinces remained in the extensive dynamic path. The energy intensity, energy-related carbon intensity, and GS structures of education contributed to the decoupling of GSP from CO2 emissions, however, GS intensity on capital-labour input delayed. Highlights: Decoupling state between government spending (GS) and CO2 emissions was discussed. Two dynamic paths of decoupling states were proposed for Chinese provinces. Four decoupling states were: weak, strong, expansive negative, and strong negative. Beijing, Tianjin, and Jilin were in the intensive dynamic path of decoupling state. GS on education promoted decoupling, however, GS on capital-labour input delayed.